POLLS ON SOCIAL MEDIA DURING THE ELECTORAL PERIOD: LEGAL LIMITATIONS AND THEIR EFFECTS ON THE FORMATION OF VOTER WILL (CIPEEX, 2025)
This paper analyzes the legal implications of publishing electoral polls on social media, particularly during the critical period of electoral campaigns, in light of current legislation, specialized doctrine, and the case law of electoral courts. Although Brazilian law clearly distinguishes between electoral surveys — subject to strict methodological and formal controls — and polls, which are informal in nature and lack statistical rigor, it is observed that, in the digital environment, this distinction is not fully perceptible to the average voter.An analysis of rulings by the Superior Electoral Court (TSE) and various Regional Electoral Courts (TREs) reveals a significant regulatory gap: while TSE Resolution No. 23,600/2019 prohibits the publication of polls in the fifteen days preceding the election, it does not establish any legal sanctions for such conduct. This undermines the effectiveness of the rule and encourages practices that may mislead voters.Such a scenario conflicts with fundamental constitutional principles of the electoral process, such as popular sovereignty, equal opportunity among candidates, and freedom of vote, while directly affecting the formation of voters’ will, especially considering the viral reach and influence of digital platforms.Thus, this study advocates for the urgent need for legislative reform, capable of establishing clear parameters for the use of polls in the digital environment, as well as proportional sanctions, in order to safeguard the integrity of the democratic process and ensure the effectiveness of constitutional electoral principles.
Keywords: Direito Eleitoral; Enquetes; Redes Sociais; Formação da vontade